2006
DOI: 10.3349/ymj.2006.47.2.243
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Anatomic Variation of Pancreatic Ductal System and Pancreaticobiliary Diseases

Abstract: The aims of this study were to identify the morphological diversities and anatomical variations of pancreatic ductal system and to define the relationships between pancreatic ductal systems, pancreaticobiliary diseases, and procedure-related complications, including post-ERCP pancreatitis. This study included 582 patients in whom both pancreatic duct (PD) and common bile duct were clearly visible by ERCP. PD systems were categorized into four types according to the relationship between common bile duct and PD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 28 publications
3
49
1
1
Order By: Relevance
“…8 . It may be mentioned that in one instance in this study, after the minor papilla had been cannulated the accessory pancreatic duct was demonstrated to be the main drainage system for that pancreas, as supported by Bang et al 19 .…”
Section: Contrast X-ray Procedures and Observationsupporting
confidence: 77%
“…8 . It may be mentioned that in one instance in this study, after the minor papilla had been cannulated the accessory pancreatic duct was demonstrated to be the main drainage system for that pancreas, as supported by Bang et al 19 .…”
Section: Contrast X-ray Procedures and Observationsupporting
confidence: 77%
“…Pancreatic duct anatomy can be categorized into four types. 5 In types A and B, Wirsung duct is the main pancreatic duct and drains into the major papilla of the duodenum. In type A, Santorini duct is obliterated or absent.…”
Section: Denouement and Discussionmentioning
confidence: 99%
“…Pancreatic ductal systems other than types A, B and C are defined as type D. In our patient, the presence of two ducts and two duodenal papillae indicates a type B or C pancreatic duct system anomaly. 5 In patients who have duodenal atresia and simultaneously have type B or type C pancreatic ductal system, duodenal atresia develops in the area between the two papillae. If the papillae are incompetent, they will allow gas to flow from the proximal duodenum into the duct of Santorini above the area of atresia, and from there gas can enter the duct of Wirsung below the atresia and flow into the distal duodenum.…”
Section: Denouement and Discussionmentioning
confidence: 99%
“…the part of the gland situated above the venous confluence, is frequently used as a site of transection by surgeons due to its thinness. Our study focuses on elucidating the anatomic and morphological features of the pancreatic isthmus as a site for surgical transection [5,11,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic duct type and distribution were classified by three blinded pancreatologists according to the classification proposed by Bang et al [11]. Results underwent Cohen’s ĸ test (correlation/reliability) between categorization pairs of the same individual.…”
Section: Methodsmentioning
confidence: 99%